Accessibility Scans and Institutional Activity: An Activity Theory Analysis. - Spinuzzi, Clay (College English, 2007)
This article presents views and insights of the author about Web accessibility, the ability for any user to read and understand a Web site with appropriate adaptive technology. Web accessibility is defined in practice, in activity, or, rather, in several overlapping activities. The author has identified several structural violations at Web site, most accessibility issues come to light through interpretive checks. The combination of structural and interpretive checks means that someone who reviews accessibility must construct reasonable arguments about whether accessibility is met in a given instance, an argument that must hold reasonably in any number of overlapping activities.